Tantangan Muhammadiyah dalam Inovasi Pendidikan Islam : Menyongsong Era Digitalisasi dengan Pengetahuan yang Berkualitas - Tiana Dwi Marisa; Dewi Sinta; Pandu Ardiansyah; Astika Nurul Hidayah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Muhammadiyah is an Islamic movement with the preaching of Amar Makruf Nahi Munkar which is based on Islamic faith and is based on the Qur'an and As-Sunnah. Many things drive the progress of this Muhammadiyah organization, such as the vision-mission, educational concept, goals, and curriculum that are mutually continuous so that Muhammadiyah can process well in the life of society. In Islamic education there are challenges that must be faced by Muhammadiyah because considering the development of Islam is very fast and also flexible and always relevant from time to time. One of the challenges to the development of Islamic education is the advancement of technology. The advancement of science and technology (iptek) requires all parties to be competent so as not to be eroded and crushed by the times. The negative and positive impacts of technological progress must be addressed with the right innovation. Innovation that can be applied by the Muhammadiyah organization is through the field of education. Education is a process that can shape human beings such as potential, personality, intelligence, noble morals, self-control, religion and skills needed in oneself and society.